FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PUBLIK DALAM ADMINISTRASI PEMERINTAHAN DI INDONESIA - Rahyunir Rauf (UIR Press, 2018)
Government in general is an organization given legitimacy by the people as the holder of sovereignty to carry out the duties of government in the country, as well as equipped with state-fittings .. The government is an organization that has; The governing authorities of a political unit, the ruling power of a political society, the apparatus is functioning government agencies and the exercise of power, the power to make laws dealing with disputes and discuss the decision of the administration with a monopoly on the legitimate power. Essential functions of government, namely; service (service), empowerment (empowerment) and development (development). Public service is a public bureaucracy production received citizen users. Related awareness of government officials towards the delivery of public services, in fact, not all government officials aware of the importance of service. In fact, sometimes the expression